The seeds of triumph : church and state in Gomułka's Poland - Diskin, Hanna (Central European University Press, 2001)
The book points to the church-state conflict in Gomulka's Poland as the catalyst for events over the following decades, and as paving the way to the dramatic changes that took place in 1989.